Multicenter analysis of attrition from the pediatric TB infection care cascade in Boston - Campbell, Jeffrey I.; Tabatneck, Mary; Sun, Mingwei; He, Wei; Musinguzi, Nicholas; Hedt-Gauthier, Bethany; Lamb, Gabriella S.; Domond, Kezia; Goldmann, Don; Sabharwal, Vishakha; Sandora, Thomas J.; Haberer, Jessica E. (The Journal of Pediatrics, 2023)
Objectives: Characterizing losses from the pediatric tuberculosis (TB) infection care cascade is important to identify ways to improve TB infection care delivery. Study design: We conducted a retrospective cohort study of children (<18 years old) screened for TB within 2 Boston-area health systems between January 2017-May 2019. Patients who received a tuberculin skin test (TST) and/or interferon gamma release assay (IGRA) were included. Results: We included 13,353 tests among 11,622 patients; 93.9% of tests were completed. Of 199 patients with positive tests for whom TB infection evaluation was clinically appropriate, 59.3% completed treatment or were recommended not to start treatment. Age 12–17 (vs <5 years; aOR 1.59 [95%CI 1.32–1.92]), non-English/non-Spanish language preference (vs English; aOR 1.34 [95%CI 1.02–1.76]), and receiving an IGRA (vs TST, aOR 30.82 [95%CI 21.92–43.34]) were associated with increased odds testing completion. Odds of testing completion decreased as census tract social vulnerability index quartile increased (i.e., social vulnerability worsened; most vulnerable quartile vs least vulnerable quartile, aOR 0.77 [95%CI 0.60–0.99]). Odds of completing treatment after starting treatment were higher among females (vs males, aOR 2.35 [95%CI 1.14–4.85]) and were lower among patients starting treatment in a primary care clinic (vs TB/infectious diseases clinic, aOR 0.44 [95%CI 0.27–0.71]). Conclusions: Among children with a high proportion of negative TB infection tests, completion of testing was high, but completion of evaluation and treatment was moderate. Transitions towards IGRA testing will improve testing completion; interventions addressing social determinants of health are important to improve treatment completion
Keywords: Latent tuberculosis; Pediatric; Care cascade; Interferon gamma release assay; Tuberculin